Празька весна 1968 р. та антирадянські ігри в козаків одеських підлітків - Хромов, А. (Чорноморська минувшина, 2018)
У статті, на основі розсекречених документів із фондів Галузевого державного архіву Служби безпеки України та Архіву тимчасового зберігання Управління Служби безпеки України в Одеській області, описана антирадянська акція одеських підлітків. Зокрема, мова йде про виготовлення ними листівки з засудженням радянської окупації Чехословаччини в 1968 р. (фотокопія листівки додається в ілюстраціях). Встановлено, що хлопець, який виготовив листівку на підтримку Празької весни 1968 р., до того разом з друзями створив «таємну» козацьку організацію. In the article on the basis of uncovered documents of KGB from the funds of the Branch State Archive of the Security Service of Ukraine and the Archive of the temporary storage of the Office of the Security Service of Ukraine in the Odessa region is described the anti-Soviet action of Odessa teenagers. In particular, the question is about their leaflet that condemned the Soviet occupation of Czechoslovakia in 1968 (a photocopy of the leaflet is in the illustrations of the article). It is established that the guy who produced the leaflet in support of the Prague Spring of 1968, before that, had created together with friends a "secret" Cossack organization. The author of the article searched and found the main person involved in the archive-criminal case. The hero refused a public interview, did not want to supplement the article with his memories. He does not consider his act to be a real act of the hero. At the same time, this incident was one of the hundreds of such protests by Soviet citizens against the occupation of Czechoslovakia in 1968. В статье, на основе рассекреченных документов из фондов Отраслевого государственного архива Службы безопасности Украины и Архива временного хранения Управления Службы безопасности Украины в Одесской области, описана антисоветская акция одесских подростков. В частности, речь идет про изготовление ними листовки осуждающей советскую оккупацию Чехословакии в 1968 году (фотокопия листовки представлена в иллюстрациях статьи). Установлено, что парень, который изготовил листовку в поддержку Пражской весны 1968 г., до этого создал вместе с друзьями «тайную» казацкую организацию.